Heating dissipation discussion of TSV-integrated ion trap with glass interposer - Zhao, Peng (2024)
In this work, we discuss the possible solutions to mitigate the temperature increase issue in TSV integrated ion trap with two approaches: (1) heat generation reduction, and (2) heat dissipation enhancement. We investigate the effect of electrical conductivity of silicon, grounding plane, number of TSV and TSV pitch towards the power loss and associated temperature increase of the ion trap. It is found that the temperature increase can be maintained below 2 K if suitable silicon substrate is used, or a grounding plane is introduced below the electrodes. As compared to the number of TSV density, the effect of TSV pitch is less significant. On the other hand, additional thermal dissipation medium is introduced apart from the original micro bumps between ion trap and interposer to enable high efficiency heat dissipation. Also, to select an appropriate interposer substrate, the relationship between the temperature increase and the thermal conductivity of interposer is evaluated. This work provides insights into the thermal management of large-scale ion trap implementation.